The Effect of Various Levels of Zinc during Gestation on Physical Growth and Development of the Offspring - Shahzad Tahmasebi; Mehdi Shahbazi; Naser Naghdi (University of Tehran, 2009)
The purpose of this study was to evaluate the effect of dietary zinc levels during gestation on physical development of offspring. The statistical population consisted of adult male and female rats (Albino-Wistar) which were obtained from Pasteur Institute, Iran. After mating, 9 pregnant female rats were divided into 3 groups: 1) Zinc deficient group (0.05